2019
DOI: 10.2147/dddt.s194961
|View full text |Cite
|
Sign up to set email alerts
|

<p>Polyphyllin VI induces apoptosis and autophagy in human osteosarcoma cells by modulation of ROS/JNK activation</p>

Abstract: PurposePolyphyllin VI, a main active saponin isolated from traditional medicinal plant Paris polyphylla, has exhibited antitumor activities in several cancer cell lines. In the present study, we investigated the antitumor effect of Polyphyllin VI against human osteosarcoma cells (U2OS) and the underlying molecular mechanisms.MethodsThe U2OS cell lines were used to determine the antiproliferative effect of Polyphyllin VI by CCK8 assay. Cell cycle was analyzed by flow cytometry. The Polyphyllin VI-induced apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
(47 reference statements)
0
26
0
Order By: Relevance
“…In this study, we found that PPVI could activate the JNK and p38 pathways, consistent with previous studies. 6,20 Furthermore, SP and SB partially attenuated the PPVIinduced effects on glioma cells, and NAC treatment attenuated JNK and p38 activation induced by PPVI. However, the levels of ROS, after SP and SB treatment, did not show an obvious change indicating that ROS could modulate the JNK and p38 pathways.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, we found that PPVI could activate the JNK and p38 pathways, consistent with previous studies. 6,20 Furthermore, SP and SB partially attenuated the PPVIinduced effects on glioma cells, and NAC treatment attenuated JNK and p38 activation induced by PPVI. However, the levels of ROS, after SP and SB treatment, did not show an obvious change indicating that ROS could modulate the JNK and p38 pathways.…”
Section: Discussionmentioning
confidence: 95%
“…15 In the current study, we describe the ability of PPVI, the main active ingredient extracted from Paris polyphylla, to exhibit cytotoxicity in various malignancies. 6,20,23,24 We reveal the anti-tumor effects of this compound, in the suppression of cell proliferation and migration, blocking cell cycle progression as well as the induction of autophagy and apoptosis. Furthermore, we show that the anti-tumor activity of PPVI in glioma cells function through the accumulation of ROS and activation of the JNK and p38 pathways.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies have shown that ROS accelerates the death of tumor cells, thereby effectively treating cancer (38,39). High production of ROS decreases the mitochondrial transmembrane potential and the release of cytochrome c, which then activates a series of caspases, thereby inducing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma is characterized by rapid proliferation and high invasiveness that pose difficulties for treatment. 16,17 Previous studies demonstrated that different subtypes of glioma exhibited significant differences in treatment and prognosis. 2,[18][19][20] Identification of effective markers that can predict the prognosis of glioma patients is essential for the development of successful treatment plans.…”
Section: Discussionmentioning
confidence: 99%